1972
DOI: 10.1002/tera.1420050213
|View full text |Cite
|
Sign up to set email alerts
|

The teratogenic activity of α thalidomide analogue, EM12, in rabbits, rats, and monkeys

Abstract: The teratogenic activity of a stable analogue of thalidomide, 2( 2,6-dioxopiperiden-2-yl)-phthalimidine ( EMIz), has been compared in monkeys, rabbits, and rats. After oral administration of 25-250 mg/kg, EMIZ was teratogenic in monkeys and rabbits but only slightly so in rats. After iv injection of the compound dissolved in dimethyl sulfoxide and water, teratogenic effects were observed both in offspring of rabbits and rats receiving doses of 10 mg/kg. The malformations observed in monkeys and rabbits were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

1982
1982
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 8 publications
0
13
0
2
Order By: Relevance
“…VPA was the drug of choice, since thalidomide has different effects in rodents than in humans (Schumacher et al, 1972). VPA, on the other hand, is a powerful teratogen in rodents and produces many of the malformations observed in humans (Binkerd et al, 1988; Collins et al, 1991; Ehlers et al, 1992).…”
Section: Vpa Exposure In Ratsmentioning
confidence: 99%
“…VPA was the drug of choice, since thalidomide has different effects in rodents than in humans (Schumacher et al, 1972). VPA, on the other hand, is a powerful teratogen in rodents and produces many of the malformations observed in humans (Binkerd et al, 1988; Collins et al, 1991; Ehlers et al, 1992).…”
Section: Vpa Exposure In Ratsmentioning
confidence: 99%
“…Since thalidomide does not have the same teratogenic effect in rodents as in primates (Schumacher et al, 1968), VPA was used to injure rats' brainstems in utero (Rodier et al, 1996(Rodier et al, , 1997. Somatic effects of VPA are known to be similar to those of thalidomide (Binkerd et al, 1988), and its teratogenic effect is also observed in human beings (Lindhout et al, 1992;Ardinger et al, 1998) also causing, in addition to somatic dysfunction, CNS dysfunction described as fetal valproate syndrome, which has recently been connected with autism (Christianson et al, 1994;Williams and Hersh, 1997;Williams et al, 2001;Moore et al, 2000;Bescoby Chambers et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the evaluation of developmental toxicity, the ICH Harmonized Tripartite Guideline, "Detection of Toxicity to Reproduction for Medical Products" (June 24, 1993), a second mammalian species traditionally has been required, with the rabbit being the referred choice as a nonrodent. Reasons for using rabbits in embryotoxicity studies include the extensive background knowledge that has been accumulated, such as availability and practicality (Christian and Hoberman, 1996;Foote, 2000;Schumacher et al, 1972). In fact, rabbits have a sensitivity to human teratogens, such as thalidomide (Fabro and Smith, 1966;Fratta et al, 1965;Schumacher et al, 1968).…”
Section: Introductionmentioning
confidence: 99%